Penerapan Metode YOLO dan Tesseract-OCR untuk Pendataan Plat Nomor Kendaraan Bermotor Umum di Indonesia Menggunakan Raspberry Pi - Eric Tirtana; Kartika Gunadi; Indar Sugiarto (Jurnal Infra, 2021)
Parking system is a common thing to find in public places. Parking system usually comes with a program that enables to detect and read license plates. With the advancement of technology, there are many systems / programs that are able to automatically detect and read license plates, but they come with a costly price. In this research, Raspberry Pi 4 will be used as the main platform. With the usage of Raspberry Pi, it is expected to reduce the cost needed to achieve the same output. However, by using Raspberry Pi, the hardware specifications are not as good as computer in general. In this research YOLO will be used to detect the license plate and Tesseract-OCR is used to read the characters on the license plate. From this research, it can be concluded that program can implement YOLO and Tesseract-OCR to detect and read public transportation license plates while being run on Raspberry Pi 4. To get the optimal results, the input image needs to be taken at daytime, using high quality camera, and implement only the necessary pre-processing methods.